ZOLEDRONIC ACID THERAPY FOR MONO-OSTOTIC LANGERHANS CELL HISTIOCYTOSIS: A CASE REPORT - Tee, Pian Pian; Ho, Wei Li Cindy (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Langerhans cell histiocytosis (LCH) is a rare disease. It can affect any organ in the body but is primarily characterized by osteolytic bony lesions. Skeletal LCH may range from a unifocal, self-limiting, asymptomatic lesion to severe, painful, destructive lesions that are prone to pathological fractures. Treatment decisions are individualized according to location, size, surgical accessibility, and functional impairment. Hence, there is no standard of care at the moment. Zoledronic acid (ZA) has been used in some neoplastic bone conditions to slow down the progression and reduce the bone pain. CASE We report a 6-year-old male with unifocal bony LCH at the left tibia who responded well to ZA. He presented at 4 years old with limping and was subsequently not ambulatory due to severe pain. He had a tender swollen left shin without skin changes. X-ray showed a poorly defined 4.7 x 1.1 cm permeative lytic lesion in the medullary cavity of the midshaft of the left tibia with endosteal thinning. Subsequent MRI and isotope bone scans (Tc-99m MDP) confirmed a suspicious primary bone malignant lesion. A bone biopsy showed a neoplastic proliferation of histiocytoid cells with strong diffuse positivity for CD 1a, which was in keeping with LCH. This confirmed a symptomatic mono-ostotic LCH with significant cortical destruction that was at risk of fracture. ZA was initiated after careful evaluation. His pain completely resolved with a return of function six weeks after the first dose of ZA. He received 4 doses of ZA in total and demonstrated radiographic evidence of regression and remained in remission. Conclusion This case demonstrates the potential role of ZA therapy as the first line treatment for mono-ostotic LCH stabilisation and symptomatic control.